Mediterranean Fast Food: A Leading Cause of Hypercholesterolemia among University Students in Northern Jordan - Moawiah Khatatbeh; Waleed Momani; Zaid Altaany; Reem Al Saad; Abdul Rahman Al Bourah; Omar Melhem; Omar AL Omari (Tehran University of Medical Sciences, 2022)
Background: Consumption of fast food is pervasive among young adults. This research aimed to assess the impact of consuming fast foods on total cholesterol level among university students in Northern Jordan. Methods: Using a cross-sectional design, a blood sample to investigate cholesterol level was drawn from a sample of university students in Northern Jordan. Besides, students' dietary habits and anthropometric measurements were obtained. Results: Out of 201 participants, 57% (n=115) were male and 43% (n=86) were female. More than three quarters of the sample ate shawarma (Mediterranean fast food) at least once per week. About 44% of the study subjects had increased BMI and about 37% had increased serum cholesterol level. Participants' gender, age, marital status, physical activity, BMI, living status, and daily pocket money significantly correlated with cholesterol level (P<0.05). In the regression analysis, eating fast foods and increased BMI were strong predictors of high cholesterol level. Students who ate shawarma more than 3 times a week had more than 8 folds to have hypercholesterolemia (OR=8.4; CI: 2.62-26.72), and obese students were more than 14 folds at higher risk to have hypercholesterolemia compared to those with normal BMI (OR=14.2; CI: 4.80-42.29). In addition, male students had doubled odds for having abnormal cholesterol level compared to females (OR=2.1; CI: 1.10-4.44). Conclusion: Fast food consumption among university students in Jordan was significantly associated with increased total cholesterol level. Encouraging healthy diet and lifestyle are the basis for prevention of dyslipidemia.